Water resources in the semi-arid Pampa–Patagonia transitional region of Argentina - Paoloni, Juan Dario (2003)
The study was carried out in the zone corresponding to the Anzoátegui district (Province of La Pampa, Argentina), covering an area of 1600km2. This zone belongs to the Caldenal or Southern Espinal, an semi-arid region in central Argentina. The annual rainfall is 109/761 mm, but the annual evapo-transpiration is as high as 1220mm, so that the annual runoff is small compared with the annual rainfall. Since shallow ground-water is the principal source of water in the region, the hydrodynamics of the subterranean flow was evaluated and the depth variation of hydrostatic levels in relation to the surface was studied. Water quality was determined by hydrochemical analyses and classified for drinking water for cattle, human consumption and irrigation. It was found to be poor, 60·2% of the study area is affected by saline concentrations exceeds 5·0dSm−1. With respect to the ground-water-quality deterioration, reference was made to land use and management systems in the area, where the main economic activity is the cattle breeding, so that the vegetation has been degraded by overgrazing and deforestation for over 100 years.